From waifus to whales: The evolution of discourse in a mobile game-based competitive community of practice. (January 2021) - Britt, Brian C.; Britt, Rebecca K.
Online communities devoted to mobile games represent exemplary examples of competitive communities of practice, leveraging the competing forces of cooperation and competition to foster in-group solidarity and motivate members to further engage with the game and community. In this study, latent Dirichlet allocation was used to model conversation topics across over two million posts and comments made during a 3-year period on the r/grandorder subreddit, a competitive community of practice devoted to the mobile game Fate/Grand Order . In total, 20 distinct topics emerged spanning topical foci and emotional tones. The prevalence of certain topics, such as those related to gacha game mechanics, declined as community members mastered the practice and as the practice itself changed. Future studies should compare the structure and evolution of conversations across contexts, and they should likewise examine differences that emerge in discourse due to the relative balance of competitive and cooperative influences.